2018
DOI: 10.1111/vop.12559
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane transplantation for ligneous conjunctivitis in a doberman

Abstract: An approximately 2-year-old female Doberman Pinscher was referred for the evaluation of bilateral, chronic proliferative conjunctivitis. Ophthalmic examination revealed bilateral thick, opaque pseudomembranes originating from the conjunctivae that prevented visualization of the cornea and interior structures of the eye. Histopathological findings of biopsies of the pseudomembranes were consistent with ligneous conjunctivitis. Serum plasminogen activity levels were within the normal range. Treatment with topica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In the above report, the AM grafts stayed in place for 2 weeks before sloughing, and remnants of AM that were present three weeks after the surgery were removed manually. After three months, the patient's conjunctival tissues returned to normal in terms of their appearance and function, and at the final follow‐up 24 months after the surgery, the patient did not exhibit any regrowth of the pseudomembranous tissue 11 . In the case described here, the AM was not removed, and correct conjunctival healing was achieved one month after the surgery.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In the above report, the AM grafts stayed in place for 2 weeks before sloughing, and remnants of AM that were present three weeks after the surgery were removed manually. After three months, the patient's conjunctival tissues returned to normal in terms of their appearance and function, and at the final follow‐up 24 months after the surgery, the patient did not exhibit any regrowth of the pseudomembranous tissue 11 . In the case described here, the AM was not removed, and correct conjunctival healing was achieved one month after the surgery.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, O’Leary et al . successfully used a cryopreserved equine AM to reconstruct conjunctival tissue after excision of pseudomembranes in a dog with ligneous conjunctivitis 11 . The AM was sutured in place with the epithelial side oriented downward in order to act as a patch ( ie , overlay technique).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical cyclosporine and heparin are relatively inexpensive and accessible, but their efficacy may be limited [ 18 , 19 ]. Amniotic membrane transplantation is more invasive and expensive than other treatment options [ 20 , 21 , 8 ]. Heterologous serum may not be readily available and may be expensive [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was recently found that the transplantation of the amniotic membrane associated with immunosuppressive azathioprine induced long‐term control of the ocular signs (O’Leary et al . 2018 ).…”
mentioning
confidence: 99%